Philosophy of education : major themes in the analytical tradition Volume III : Society and education (London ; New York : Routledge, 1998)
Democracy, pluralism and education. Justice, equality and education. Education, schooling and rights. Society and schooling.
Keywords: Education; Critical pedagogy; Philosophy; Education -- Philosophy; Critical pedagogy -- Philosophy; Educational sociology